2004
DOI: 10.1081/dct-120027895
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fosphenytoin on Nerve Agent‐InducedStatus epilepticus

Abstract: This study evaluated the effectiveness of fosphenytoin as a single or adjunctive anticonvulsant treatment for nerve agent-induced status epilepticus. Guinea pigs, implanted with cortical electroencephalographic (EEG) recording electrodes, were pretreated with pyridostigmine bromide (0.026 mg/kg, intramuscular (i.m.)) 30 min before challenge with 56 micrograms/kg, subcutaneous (s.c.), (2 x LD50) of the nerve agent soman. One min after soman, the animals were treated (i.m.) with 2 mg/kg atropine sulfate admixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Thirty min after pyridostigmine the animals were challenged SC with 56 ug/kg soman (2 X LD50) and one min later were treated IM with the admixed 2.0 mg/kg atropine and 25.0 mg/kg 2-PAM. This procedure results in seizures in 100% of animals tested in multiple studies (McDonough et al, 1999(McDonough et al, , 2000(McDonough et al, , 2004Capacio et al, 2003Capacio et al, , 2004. The animals were then monitored for seizure onset by a technician and the investigator, who were well-experienced with the appearance of nerve agent-induced EEG seizure activity in guinea pigs.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty min after pyridostigmine the animals were challenged SC with 56 ug/kg soman (2 X LD50) and one min later were treated IM with the admixed 2.0 mg/kg atropine and 25.0 mg/kg 2-PAM. This procedure results in seizures in 100% of animals tested in multiple studies (McDonough et al, 1999(McDonough et al, , 2000(McDonough et al, , 2004Capacio et al, 2003Capacio et al, , 2004. The animals were then monitored for seizure onset by a technician and the investigator, who were well-experienced with the appearance of nerve agent-induced EEG seizure activity in guinea pigs.…”
Section: Methodsmentioning
confidence: 99%
“…For each animal in which the seizure was terminated, the latency to seizure termination was measured as the time from when the animal received gabapentin treatment to the last observable epileptiform event in the EEG. These evaluation procedures and operational criteria for seizure control are identical to those used in previous studies utilizing this animal model (McDonough et al, 1999(McDonough et al, , 2000(McDonough et al, , 2004Capacio et al, 2003Capacio et al, , 2004Shih et al, 2003Shih et al, , 2007.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal experiments have clearly shown that these seizures will not stop without industrial-strength doses of phenytoin, phenobarbital, lamotrigine, carbamazepine, or valproic acid. 28,29 The reason for this may lie in the wide anatomic distribution of the cholinergic system within human brain. Effectively, status in nerve agent poisoning is extremely multicentric, and thus drugs which work, at least in part, by dampening the spread of seizure discharges are ineffective.…”
Section: Oximesmentioning
confidence: 99%